Effects of an empathy enhancement program using patient stories on attitudes and stigma toward mental illness among nursing students - Cho, Mi-Kyoung; Kim, Mi Young (Frontiers in Psychiatry, 2024)
Objective: This study aims to explore the impact of an empathy intervention through patients’ stories and investigate its impact on attitudes and stigma toward mental illness among nursing students prone to hold prejudices against this condition. Method(s): Using a quasi-experimental pretest-posttest design, this study focused on nursing students and examined the effects of an empathy enhancement program targeting individuals with mental illnesses on communication, social distance, and prejudice. Ninety third-year nursing students from S and C cities and H and C universities enrolled in psychiatric nursing courses participated in the study. The intervention lasted four weeks and used the patient’s story to facilitate a participatory approach to understanding the patient’s life and encouraging mutual growth and expansion of consciousness in the therapeutic relationship. Age was treated as a covariate and analyzed using a two-way repeated-measure analysis of covariance. Result(s): The Empathy Enhancement Program Using Patient Stories (EEP-PS) group and the clinical practicum group showed no significant differences in communication, social distance, and empathy scores between the two groups or across different time points. However, variations were observed when examining specific subdomains within each group and across time points. Informative communication (F = 10.34, p = .002) and affiliative communication (F = 21.60, p < .001), which are subcategories of communication, increased significantly in the posttest compared to the pretest. Among social distances, interpersonal-physical distance decreased significantly in the posttest compared to the pretest (F = 31.02, p < .001). Prejudice of incompetence (F = 6.52, p = .012) and prejudice of risk (F = 14.37, p < .001) were significantly lower in the posttest than in the pretest. Conclusion(s): Both the EEP-PS and clinical practicum groups experienced improvements in communication, social distance, and prejudice toward individuals with mental illness. This study suggests that direct patient interactions and the use of patient narratives as indirect methods are effective approaches for enhancing attitudes and reducing stigma toward mental illness among nursing students.